DCI Banks. Season five [videorecording (DVD)] - Tompkinson, Stephen, 1965-; Lowe, Andrea, 1975-; Catz, Caroline (BBC Worldwide, 2017)
Some stories include: When a young man is found brutally murdered, Banks' instinct drags his team into a world of organized crime. The apparent suicide of a young girl drags Banks deeper into the dark world of 'untouchable' criminal Steve Richards. When a devoted husband and father goes missing, a ransom demand takes Banks and his team on a journey into the Chinese community.